Professional Learning for Teaching Assistants and its Effect on Classroom Roles - Hurst, Chris; Sparrow, Len (Mathematics Education Research Group of Australasia Inc, 2012)
The Swan Valley Cluster of schools for the Make It Count project identified the professional learning of teachers and teaching assistants as a key factor in improving numeracy outcomes for urban Indigenous children. Initial training for assistants began in late 2010 and took the form of workshops based on a modified First Steps in Mathematics Number program. It was continued in 2011 and lead to a pilot program in training assistants to plan for targeted mathematics learning for individuals and small groups of children. This paper reports on the success of the pilot with regard to the improved confidence and ability of the assistants to assume greater responsibility for teaching, as well their development as integral members of professional learning communities.